THE ROLE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN IMPROVING STUDENTS' LEARNING MOTIVATION AT MTSS LAM UJONG ACEH BESAR - Hadi, Abdul; Miswar, Miswar; Gadeng, Banta (Journal of Learning on History and Social Sciences, 2024)
Islamic Religious Education teachers at MTsS Lam Ujong play a key role in increasing students' learning motivation. Through inspiring teaching, providing real examples, and moral and spiritual support, Islamic Religious Education teachers help create a generation of students who are not only academically intelligent, but also strong in religious and moral values. This research is a qualitative. The approach used in this research is a field research approach. The research results show that 1). The role of Islamic Religious Education teachers in increasing students' learning motivation at MTsS Lam Ujong Aceh Besar is that PAI teachers play an important role in building students' learning motivation through a holistic approach. Islamic Religious Education teachers not only teach religious material, but also become moral guides and inspirators who motivate students emotionally and spiritually. Factors such as varied teaching methods, good relationships between teachers and students, and support from the school environment and family, greatly influence the effectiveness of the teacher's role in improving students' learning motivation and 2). Factors that influence the effectiveness of the role of Islamic Religious Education Teachers in improving students' learning motivation at MTsS Lam Ujong Aceh Besar are that the effectiveness is influenced by several main factors, such as the quality of teacher-student relationships, varied teaching methods, teacher competence and skills, and support from family and the school environment. In addition, the availability of adequate facilities and infrastructure and the psychological condition of students also play an important role in determining the extent to which PAI teachers can motivate students to learn optimally.